Nanomedicine: A modern advent for combating COVID-19 - Muhammad Ahsan Khan; Ahya; Siddiqui, Mishal Shan (Journal of the Pakistan Medical Association, 2022)
Madam, Our current understanding of the COVID-19 virus and its vulnerabilities has not been translated into the approval of its standard line of treatment. COVID-19, although primarily a respiratory ailment, may culminate in acute respiratory distress syndrome, hyperinflammatory response, sepsis, and multiorgan failure, which often carry a grave prognosis. Drugs addressing such severities of COVID-19 are often limited by their therapeutic indices, bioavailability, and side effects, necessitating the exploration of new avenues to counter them. The ever-evolving field of nanotechnology presents one such example.